Improving The Students’ Speaking Achievement in Narrative Text Through Snowball Throwing Model - Ira Pane (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2014)
This study was conducted to discover students’ achievement in narrative text through snowball throwing model. The design of this study was Classroom Action Research (CAR). The subject of this study was the students of Grade VIII, 2013/2014 school year of SMP Swasta Taman Harapan Medan. The number of students was 39 students. The research was conducted in to two cycles and each cycle consisted of three meeting which consisted of four stages, namely: planning, action, observation, and reflection. To collect the data the instruments that used were qualitative and quantitative data. The qualitative data were collected by using diary notes, observation sheet, and questionnaire sheet. The quantitative data were collected by giving speaking test. Based on the data, the students’ score in speaking test got improvement in every cycle. In Test I, the mean of the students’ score was 64.44 while in Test II, the mean of the students’ score was 68.92 and in Test III, the mean of students’ score was 74.15. Based on the result of quantitative data, it was found that there was improvement on students’ speaking achievement in narrative text. Keyword:Narrative  text, snowball throwing model, classroom actionresearch